2009
DOI: 10.2169/internalmedicine.48.1659
|View full text |Cite
|
Sign up to set email alerts
|

Class III .BETA.-Tubulin Expression in Tumor Cells is Correlated with Resistance to Docetaxel in Patients with Completely Resected Non-Small-Cell Lung Cancer

Abstract: Objective To assess the relationship between in vitro chemosensitivity evaluated by the histoculture drug response assay (HDRA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…Similarly, low β-tubulin III expression was associated with improved outcome after taxane-based neoadjuvant chemotherapy and surgical resection in a cohort of Korean patients [53]. Several other studies in agreement with these results have been reported, suggesting a potential use of β-tubulin III expression as a tool to select patients [10, 54,55].…”
Section: Taxanessupporting
confidence: 58%
“…Similarly, low β-tubulin III expression was associated with improved outcome after taxane-based neoadjuvant chemotherapy and surgical resection in a cohort of Korean patients [53]. Several other studies in agreement with these results have been reported, suggesting a potential use of β-tubulin III expression as a tool to select patients [10, 54,55].…”
Section: Taxanessupporting
confidence: 58%
“…Briefly, fresh tumour specimens were cut into small pieces of approximately 10 mg and then placed on prepared collagen surfaces in 24-well microplates. After treatment with docetaxel and cisplatin at the concentration of 100  μ g ml –1 (Hayashi et al , 2009) and 20  μ g ml –1 (Fujita et al , 2009), respectively, 3-(4,5-dimethyl-2-thiazotyl)-2,5-diphenyl-2H-tetrazoliumbromide assay was used to examine cytotoxicity. The inhibition rate was calculated as previously reported (Shen et al , 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Hayashi et al [27] provided evidence that ␤III tubulin expression is predictive of poorer outcomes following taxane-based therapy, but not following gemcitabine therapy, in patients (N = 58) with completely resected NCSLC. As observed in the advanced disease setting, these data suggest that ␤III tubulin expression has predictive value for response to taxanes.…”
Section: Clinical Evidencementioning
confidence: 99%